Microfungi on the Pandanaceae: Linocarpon lammiae sp. nov., L. siamensis sp. nov. and L. suthepensis sp. nov. are described with a key to Linocarpon species from the Pandanaceae - Thongkantha S. (2014)
Linocarpon species are reported from Pandanaceae in Australia, Brunei, Hong Kong, Nepal, New Zealand, Philippines, Seychelles, Thailand and Vanuatu. Linocarpon lammiae sp. nov. were collected on decaying leaves of Pandanus tectorius in Hong Kong. Linocarpon siamensis sp. nov. and L. suthepensis sp. nov. were collected from decaying leaves of P. penetrans in Thailand. These taxa are described, illustrated and compared with Linocarpon species with similar ascospore morphology and dimensions. Included are a synoptic table, which compares the new species to similar known species, and a dichotomous key to species of Linocarpon known from members of the Pandanaceae.